Characteristics of dolomite karstic reservoir in the Sinian Dengying Formation, Sichuan Basin - Xiuqin Shan (Petroleum Research, 2017)
The Sinian dolomite reservoir in Dengying Formation was developed extensively in the Sichuan Basin, and typically was the facies-controlled dolomite karstic reservoir. The development of this kind of the reservoir was related with the special deposits, diagenetic environment as well as the multi-phase and multi-type dissolution and fracturing actions. The arid-hot/dry paleo-climate was favourable to develop the large-scale microbial reef-shoal bodies and mound–shoal bodies, which was characterized by the organic framework and the sea floor hardening, thus forming primary matrix pore-type reservoir. In the background of the arid-hot/dry paleo-climate, the water-rock interaction was weak, the mineral stabilization process was slowly, and the vadose pisoliths, aragonite and high-magnesium calcite were well preserved, therefore, this diagenetic environment especially was beneficial for pore preservation. Moreover, the syngenetic and penecontemporaneous dissolution, especially three phases of weathered crust karstification due to three episodes of the Tongwan movement, led to further dissolution of spaces and form numerous non-fabric selective dissolution fractures and dissolution caves along faults and fractures. Multi-phase fractures, especially the late Yanshanian-Himalayan tectonic fractures, resulted in connection among pores, vugs and dissolution caves, and improved quality of the reservoir tremendously. Keywords: Dolomite karstic reservoir, Reservoir space, Diagenetic environment, Dissolution, Tongwan movement, Dengying Formation, Sichuan Basin